Skogsmarksgödsling - Bergsten, Marcus (2005)
The purpose of this study is to analyze the economic effects of different fertilization programs both on stand- and forest-level. The study is applied on an objective sample of inventory data for a forest area in Kalix in northern Sweden. The forest area belongs to the forest company Sveaskog. The study includes different economic models and will be used as a support when the company decides how to invest and how much to invest in fertilization.